Beyond nuclear deterrence : transforming the U.S.-Russian equation - Arbatov, A. G. (Alekseĭ Georgievich), 1951-; Dvorkin, Vladimir; Evseev, Vladimir (Carnegie Endowment for International Peace, 2006)
"Arbatov and Dvorkin assess the history of deterrence between the Soviet Union and the U.S. and its evolution through the Cold War. The two countries need to take steps to remove mutual nuclear deterrence as the foundation of their strategic relationship and implement changes that can be exported internationally"--Provided by publisher